2018
DOI: 10.2147/cmar.s170064
|View full text |Cite
|
Sign up to set email alerts
|

Behavior change techniques for increasing physical activity in cancer survivors: a systematic review and meta-analysis of randomized controlled trials

Abstract: PurposeThe purpose of this systematic review and meta-analysis is to investigate how physical activity (PA) can be effectively promoted in cancer survivors. The effect of PA-promoting interventions in general, behavior change techniques (BCTs), and further variables as moderators in particular are evaluated.MethodsThis study included randomized controlled trials of lifestyle interventions aiming at an increase in PA that can be carried out independently at home, published by December 2016, for adults diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 99 publications
9
101
1
Order By: Relevance
“…Our results are in contrast with previous studies, where self-regulatory BCTs were found to be associated with higher adherence to exercise interventions in patients with cancer. 17 , 20 However, it is important to take into account that all groups in the Phys-Can study were provided with evidence-based support such as supervision, instructions on how to exercise, graded tasks, self-registration of exercise, feedback on exercise behavior as well as social support from coaches and peers. 16 , 17 , 19 , 21 This was done to ensure that all participants achieved a minimum exercise volume in order to detect possible effects of exercise intensity on the Phys-Can study’s main outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are in contrast with previous studies, where self-regulatory BCTs were found to be associated with higher adherence to exercise interventions in patients with cancer. 17 , 20 However, it is important to take into account that all groups in the Phys-Can study were provided with evidence-based support such as supervision, instructions on how to exercise, graded tasks, self-registration of exercise, feedback on exercise behavior as well as social support from coaches and peers. 16 , 17 , 19 , 21 This was done to ensure that all participants achieved a minimum exercise volume in order to detect possible effects of exercise intensity on the Phys-Can study’s main outcome.…”
Section: Discussionmentioning
confidence: 99%
“… 13 - 15 However, recent reviews indicate that patients with cancer may benefit from behavioral interventions promoting physical activity and exercise. 16 , 17 Such interventions typically involve strategies to facilitate exercise, including the use of behavior change techniques (BCTs), defined as active ingredients or practical components of an intervention designed to change a behavior. 18 A taxonomy of 93 BCTs has been developed by Michie et al 18 to provide a standardized method of classifying such intervention components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The term cancer survivor can be applied to an individual from the point of cancer diagnosis throughout the remainder of life. 3,4 The long-term and latent effects of cancer and its treatment can pose a number of challenges for these individuals including reductions in physical function and quality of life, the presence of cancer-related fatigue, increased risk of cancer morbidity and mortality, and increased risk for the development of other chronic conditions (eg, cardiovascular diseases, osteoporosis). [5][6][7][8][9] To assist in addressing many of these negative consequences and to support the optimization of physical and psychosocial well-being, the inclusion of physical activity (PA) as an adjunct to cancer treatment has been advocated.…”
Section: Introductionmentioning
confidence: 99%
“…[24,38]. Although there is evidence that specific changes in behavior can lead to better outcomes for survivors [21] -e.g., changes in diet, moderate exercise, cognitive therapies-in practice, it is difficult to adapt these recommendations to individual needs, preferences, expectations, and motivation factors.…”
Section: Case Study Scenario: Trajectories Of Cancer Survivorsmentioning
confidence: 99%